Kesenjangan dalam Pembangunan Kewilayahan - Saratri Wilonoyudho (Universitas Muhammadiyah Surakarta, 2009)
The purpose this paper is to provide a broad overview of the recent patterns and trends of urban growth, and to discuss the relationship between urbanization and regional imbalances in Indonesia, and also to assess the policy implication. Over the last 20 years many urban areas have experienced dramatic growth, as a result of rapid population growth and as the world‘s economy has been transformed by a combination of rapid technological and political change. The population of the cities roughly doubles when we add the zones to the metropolitan core. In the cases of Semarang, there is much more than a doubling. The inner zones are where the action is migrant come there from both the core and elsewhere in the country. Net migration in many cases contributes as much as two thirds of the population growth in these zones, whereas in the city cores, net migration contributes little to growth. A comprehensive model suggest that regional imbalances in Indonesia is influenced by economic-structural and social demographic factors.